Smart Parenting in the Digital Era: A Literature-based Framework for Enhancing Emotional Development in Early Childhood - Isobeliana Musrini; Erwin Bunga Sapan (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study aims a conceptual framework of Smart Parenting to support emotional development in early childhood within the context of the digital era. Using a qualitative literature review, 20 selected studies published between 2010 and 2023 were analyzed to identify key themes. The findings reveal that Smart Parenting combines emotional responsiveness, digital literacy, and cultural sensitivity. Emotionally attuned parenting, enhanced by appropriate digital tools to fosters emotional intelligence, empathy, and regulation skills in children. However, unsupervised or excessive screen use can hinder emotional bonding. Cultural context also shapes how Smart Parenting is practiced, highlighting the need for adaptable strategies that respect local values and resources. This framework offers a holistic approach to parenting that bridges traditional interaction with modern technology. The study contributes to parenting science by integrating digital tools, emotional neuroscience, and cultural dimensions into a unified model. It offers insights for parents, educators, and policymakers to promote healthy emotional growth in early childhood.